Pembelajaran Sosial dalam Pelaksanaan Hukuman Cambuk - Wahyuni Wahyuni; Haiyun Nisa (Fakultas Psikologi Universitas Islam Negeri Maulana Malik Ibrahim, 2021)
Abstract: Caning is a corporal punishment imposed on violators of Islamic Law in Aceh. Caning is determined based on the Quran and Hadith under the auspices of the Law to provide a deterrent effect for suspects and social learning for the whole community. The purpose of this study to describe social learning in the implementation of caning is viewed from the background of the preparation of the Qanun Jinayat and the implementation process. Data collection is done by the interview technique involving four respondents, namely two people who compiled the Qanun Jinayat and two other key informants from relevant agencies directly involved in the execution of caning. Respondents were selected using a purposive sampling technique. The results have shown that the social learning in the implementation of caning is interpreted by a decrease in the number of violations of Islamic Law in Aceh. Social learning in question is that people who watch caning will not commit the same offence, and the suspect who has been sentenced will not repeat the offence because of shame.Keywords:Caning; Social Learning; PsychologyAbstrak:Hukuman cambuk adalah hukuman badan yang diberlakukan bagi para pelanggar Syariat Islam di Aceh. Hukuman cambuk ditetapkan berdasarkan Al-Quran dan Hadist di bawah naungan Undang-Undang dengan tujuan memberikan efek jera bagi tersangka dan pembelajaran sosial bagi seluruh masyarakat. Penelitian ini bertujuan untuk menjelaskan pembelajaran sosial dalam pelaksanaan hukuman cambuk yang ditinjau dari latar belakang penyusunan Qanun Jinayat dan proses pelaksanaannya. Pengumpulan data dilakukan dengan teknik wawancara dengan melibatkan empat responden yaitu dua orang sebagai penyusun Qanun Jinayat dan dua orang lainnya informan kunci dari instansi terkait yang terlibat langsung dalam pelaksanaan hukuman cambuk. Responden dipilih menggunakan teknik purposive sampling. Hasil penelitian menunjukkan bahwa pembelajaran sosial dalam pelaksanaan hukuman cambuk dimaknai dengan adanya penurunan angka pelanggaran Syariat Islam di Aceh. Pembelajaran sosial yang dimaksud adalah masyarakat yang menonton hukuman cambuk tidak akan melakukan pelanggaran yang sama dan tersangka yang sudah dihukum tidak akan mengulangi perbuatan pelanggaran karena malu.Kata Kunci: Hukuman Cambuk; Pembelajaran Sosial; Psikologi